i need to find the inverse of f(x) = x^2-4x+3 how do you do it when you have x^2 and x?
$\displaystyle y = x^2 - 4x + 3
$
$\displaystyle y = x^2 - 4x + 4 + 3 - 4$
$\displaystyle y = (x - 2)^2 - 1$
swap x and y ...
$\displaystyle x = (y - 2)^2 - 1$
$\displaystyle x + 1 = (y - 2)^2$
$\displaystyle \pm \sqrt{x+1} = y - 2$
$\displaystyle y = 2 \pm \sqrt{x+1}$
restrict the domain of the original function to $\displaystyle x \ge 2$, and the inverse function is $\displaystyle f^{-1}(x) = 2 + \sqrt{x+1}
$